Plant competitive interactions and invasiveness: searching for the effects of phylogenetic relatedness and origin on competition intensity - Dostál, Petr (The American naturalist, 2011)
The invasion success of introduced plants is frequently explained as a result of competitive interactions with native flora. Although previous theory and experiments have shown that plants are largely equivalent in their competitive effects on each other, competitive nonequivalence is hypothesized to occur in interactions between native and invasive species. Small overlap in resource use with unrelated native species, improved competitiveness, and production of novel allelochemicals are all believed to contribute to the invasiveness of introduced species. I tested all three assumptions in a common-garden experiment by examining the effect of plant origin and relatedness on competition intensity. Competitive interactions were explored within 12 triplets, each consisting of an invasive species, a native congeneric (or confamilial) species, and a native heterogeneric species that are likely to interact in the field. Plants were grown in pots alone or in pairs and in the absence or the presence of activated carbon to control for allelopathy. I found that competition intensity was not influenced by the relatedness or origin of competing neighbors. Although some exotic species may benefit from size advantages and species-specific effects in competitive interactions, none of the three mechanisms investigated is likely to be a principal driver of their invasiveness.
Keywords: feromony; fylogeografie; Pheromones; Phylogeography; zavlečené druhy; Phylogeny; fylogeneze; Introduced Species; Magnoliopsida